She rides shotgun - Harper, Jordan (Ecco, an imprint of HarperCollinsPublishers, 2017)
When enemies from his time in prison put a bounty on his head and target his family, Nate McClusky takes his eleven-year-old daughter Polly from in front of her school into a world of robbery, violence, and the constant threat of capture, or death.